Valutazione Del Benessere Psico-Fisico Nell'aderenza Terapeutica Nelle Donne Con Malattia Renale Policistica Autosomica Dominante: Uno Studio Osservazionale. Issue 3 (September 2019) - Brioni, Elena; Magnaghi, Cristiano; Delli Zotti, Giulia Bruna; Sangiovanni, Eleonora; Sciarrone Alibrandi, Maria Teresa; Apuzzo, Luigi; Manunta, Paolo; Logias, Francesco; Burrai, Francesco
Evaluation Of The Psychophysical Well-Being In The Compliance Of Women With Autosomal Dominant Policystic Kidney Disease: An Observational Study BACKGROUND: Autosomal dominant polycystic kidney disease is the most common inherited renal disease and affects less than 1 every 400-1, 000 people. There are many effective treatments, including blood pressure management, physical activity, low sodium diet and hydration. Therapeutic education is part of a patient's care and treatment. This approach is an essential strategy in order to face the current healthcare scenario, in which the number of people affected by chronic diseases is progressively increasing. OBJECTIVES: This article aims to analyze the effect of therapeutic education in patients with ADPKD, the level of adherence to pharmacological therapy and their compliance to dietetic and lifestyle recommendations as part of a nursing-led education. METHODS: This is a prospective, longitudinal, observational pilot study. The following measurements were used: Kidney Disease Quality of life - Short Form, Hospital Anxiety and Depression Scale, Body Uneasiness Test. At the T0 visit, a nurse selected patients and carried out a personalized educational intervention with the aims of adhering to drug therapies, monitoring blood pressure and dietary behavior (physical activity and water intake). At the T1 visit, patients performed psychological tests. At the T2 visit, the following evaluations were performed: a psychological interview together with the delivery and evaluation of the tests performed, an interview with the nurse to evaluate the adherence to the prescriptions, and a control of parameters such as physical activity, diet, water intake, drug therapy, and blood pressure. RESULTS: Therapeutic education can have a positive impact on patients' health by improving adherence to the pharmacological therapy, diet and lifestyle. CONCLUSIONS: Therapeutic education improve the patient's knowledge, treatments and correct behaviors as well as promotes an independent management of the disease. Through an educational intervention, the patient acquires the ability and the awareness to modify the wrong behaviors and to guarantee a balance between his needs and the pathology, thus improving the quality of life.